1999
DOI: 10.1076/stra.7.2.103.650
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin in childhood strabismus

Abstract: The use of botulinum toxin A (BTXA) in childhood strabismus is still a matter of debate. This study investigates the indications for and outcome of BTXA therapy in children at our institution. From 1985 to 1995, 237 children up to and including 16 years of age were treated with BTXA for strabismus. We undertook a retrospective study of 163 (69%) children from this group. Factors considered were age; anaesthesia; number of, indication for and outcome of injections; complications and follow-up. There were three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 4 publications
1
18
1
Order By: Relevance
“…There have been several reports in children (Ing, 1993;McNeer et al, 1998;Scott et al, 1989;Spencer et al, 1997). Rayner et al (1999) suggested that, in particular, children with decompensating intermittent exotropias and postoperative consecutive esotropias with a potential for binocularity were most likely to benefit. There are but a few studies that discuss the utility of botulinum toxin to cure adult decompensated squint (Rowe & Noonan, 2007;Rowe et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…There have been several reports in children (Ing, 1993;McNeer et al, 1998;Scott et al, 1989;Spencer et al, 1997). Rayner et al (1999) suggested that, in particular, children with decompensating intermittent exotropias and postoperative consecutive esotropias with a potential for binocularity were most likely to benefit. There are but a few studies that discuss the utility of botulinum toxin to cure adult decompensated squint (Rowe & Noonan, 2007;Rowe et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…This also serves to prevent medial rectus contracture [5•, Class I]. Another indication for chronic botulinum use is in patients considered poor surgical candidates and surgically overcorrected patients [6,7,Class III].…”
Section: Opinion Statementmentioning
confidence: 99%
“…76 Side effects include transient ptosis, subconjunctival hemorrhage, and hypotropia. 74 Bilateral lateral rectus injections have been used for the treatment of childhood intermittent exotropia. 80 Although orthophoria was obtained in 69% of patients, these results are not as successful as those obtained with treatment of infantile esotropia.…”
Section: Strabismus In Childrenmentioning
confidence: 99%
“…68,69 Successful results have been obtained after botulinum toxin A injections for infantile esotropia. [70][71][72][73][74][75][76][77][78][79] Intervention before 7 months of age in congenital esotropia provides better results of long-term alignment 71 and as many as 66% of patients can develop stereopsis, with early treatment. 76 Side effects include transient ptosis, subconjunctival hemorrhage, and hypotropia.…”
Section: Strabismus In Childrenmentioning
confidence: 99%